2019
DOI: 10.1111/apa.15108
|View full text |Cite
|
Sign up to set email alerts
|

Usability and acceptability of an automated respiratory rate counter to assess childhood pneumonia in Nepal

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Performance of automated RR counting with ChARM was similar to the one of the Masimo Rad G pulse oximeter, with a mean difference of −1.1 breath per minute, wide 95% CI limits of agreement (−19.6-17.4 breaths/min), a kappa-statistic of 0.65 and a positive percent agreement of 81.5% [20]. Moreover, usability studies have shown that it also performed slowly with a mean performance time of more than three minutes [17,19] and the important limitation that breathing rates often increased after its application around the child's chest due to agitation [18].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Performance of automated RR counting with ChARM was similar to the one of the Masimo Rad G pulse oximeter, with a mean difference of −1.1 breath per minute, wide 95% CI limits of agreement (−19.6-17.4 breaths/min), a kappa-statistic of 0.65 and a positive percent agreement of 81.5% [20]. Moreover, usability studies have shown that it also performed slowly with a mean performance time of more than three minutes [17,19] and the important limitation that breathing rates often increased after its application around the child's chest due to agitation [18].…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, UNICEF launched the acute respiratory infection diagnostic aid (ARIDA) project and determined the target product profile of an automated RR counter [13]. Recently, two automated RR counters, i.e., a photoplethysmography-based (Masimo Rad G) [14][15][16] and accelerometer-based (Philips ChARM) [17][18][19][20] device have been evaluated in a low-resource setting. These studies revealed variable accuracy and some usability issues, such as slow performance and measurement failure [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 Other authors have used automatic respiratory rate counters; however, they are not universally available and require cost-effectiveness studies. 22 23 It has also been previously shown that the sensitivity and specificity of caregivers is insufficient to recognise tachypnoea and signs of respiratory distress in respiratory diseases and pneumonia. 24 …”
Section: Discussionmentioning
confidence: 99%
“…The usability and acceptability of this device have been tested in a study in Ethiopia 15 and Nepal. 16…”
Section: Introductionmentioning
confidence: 99%